2007
DOI: 10.1075/cilt.290.16war
|View full text |Cite
|
Sign up to set email alerts
|

A prosodic feature that invites back-channels in Egyptian Arabic

Abstract: One of the signs of listening attentively and supportively is occasional back-channel feedback, small utterances produced by the listener while the speaker continues his turn. To do this appropriately it is necessary to understand when back-channels are and are not welcome. In Egyptian Arabic, times when the listener is especially welcome to back-channel are indicated by various prosodic features produced by the speaker, including a steep pitch downslope. This particular feature contrasts with the downward pit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…In [16], it was reported that increases in pitch and intensity, as well as certain POS patterns, are key back-channel-inviting cues in taskoriented dialog. The multi-lingual comparison discussed in [5,6,7] found that pitch patterns, e.g., periods of low pitch or drops in pitch, are positively associated with listener back-channels in Japanese-, English-, Arabic-and Spanish-speakers. Recently, [17] investigated cultural differences in gaze, proxemics, and back-channel behavior in a multi-modal corpus of American English, Mexican Spanish, and Arabic speakers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [16], it was reported that increases in pitch and intensity, as well as certain POS patterns, are key back-channel-inviting cues in taskoriented dialog. The multi-lingual comparison discussed in [5,6,7] found that pitch patterns, e.g., periods of low pitch or drops in pitch, are positively associated with listener back-channels in Japanese-, English-, Arabic-and Spanish-speakers. Recently, [17] investigated cultural differences in gaze, proxemics, and back-channel behavior in a multi-modal corpus of American English, Mexican Spanish, and Arabic speakers.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has identified cross-cultural differences in a variety of behaviors that may play a role in signaling mutual engagement, endorsement or appreciation. These behaviors include nodding [1], posture [2], facial expression [3], gaze [4], cues to vocal back-channel [5,6,7], nonverbal back-channel [8]), and coverbal gesturing [9] as well.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, related research on gaze so far has been mainly concerned with the analysis and modeling of dyadic interaction rather than multi-party interaction and has not focused on the role of the listener in particular (Argyle and Cook, 1976;Vertegaal et al, 2001;Vinayagamoorthy et al, 2004;Jaffe et al, 1973;Ruhland et al, 2015;Andrist et al, 2017;Mutlu et al, 2006). Similarily, also research on feedback token has mainly focused on analyzing dyadic interactions e.g., (Kawahara et al, 2016;Ward et al, 2007) and on modeling the timing of feedback token therein (Morency et al, 2010). Which modality should be chosen, audio or visual, and how feedback tokens are combined with gaze has not been the focus of research so far.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, he suggested a well-made system, which produces a back channel item after a low pitch region of a certain frequency. Ward & Al Bayyari (2007) have also introduced various prosodic features in the speakers' speech signaling the appropriate times of back channeling in Egyptian Arabic, including a pitch upturn at the phrasal end, low flat pitch associated with a lengthened vowel at dis-fluency points, and a sharp pitch downslope.…”
Section: Linguistic Discovery 102:109-118mentioning
confidence: 99%